The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1152/ajplung.1996.271.1.l70
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Na-K-ATPase activity after prolonged hypoxia in an alveolar epithelial cell line

Abstract: Exposure to alveolar hypoxia may induce acute pulmonary edema. Because the vectorial sodium transport by alveolar epithelium represents an important mechanism for alveolar edema clearance, we examined whether hypoxia affects Na-K-ATPase activity in cultured SV40-transformed rat alveolar type II cells (SV40 ATII cells). Hypoxic exposures (O or 5% O2 for at least 12 h) induced a time- and O2 concentration-dependent decrease in ouabain-sensitive rubidium (osRb) influx. Neither the sensitivity of Rb influx to ouab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 0 publications
0
46
0
Order By: Relevance
“…ATP homeostasis in hypoxia has been explained in many cases as resulting from inhibition of energy-consuming processes. In ATII cells, activity of the Na ϩ -K ϩ -ATPase in maintenance of fluid homeostasis may account for as much as 20% of cellular ATP demand, with prior work demonstrating suppression of this process in hypoxia (10,27). Hypoxic ATII cells undergo endocytosis and degradation of this plasma membrane-associated Na ϩ -K ϩ -ATPase, resulting in a large decrease in the necessity of the cell to produce ATP to maintain bioenergetic homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…ATP homeostasis in hypoxia has been explained in many cases as resulting from inhibition of energy-consuming processes. In ATII cells, activity of the Na ϩ -K ϩ -ATPase in maintenance of fluid homeostasis may account for as much as 20% of cellular ATP demand, with prior work demonstrating suppression of this process in hypoxia (10,27). Hypoxic ATII cells undergo endocytosis and degradation of this plasma membrane-associated Na ϩ -K ϩ -ATPase, resulting in a large decrease in the necessity of the cell to produce ATP to maintain bioenergetic homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In alveolar epithelial type II cells, hypoxia decreases Na-K-ATPase mRNA expression and activity [15]. It has been suggested that alveolar epithelial type II cells exposed to hypoxia may release a soluble factor that inhibits Na-K-ATPase activity [28]. Interestingly, highaltitude exposure stimulates the release of an endogenous digoxin-like factor, which may have inhibitory effects on transepithelial sodium transport [29].…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to occur in alveolar epithelial cells (Planès et al, 1996;Dada et al, 2003) via an HIF-1␣ independent mechanism , and is thought to contribute to pulmonary edema under hypoxic conditions. Our experiments have demonstrated that hypoxia mediated regulation of Na ϩ /K ϩ ATPase also occurs in DRG neurons also.…”
Section: Effects Of Endoneurial Hypoxia On the Namentioning
confidence: 99%